Holy Legionary Youth : Fascist Activism in Interwar Romania - Clark, Roland (Book collections on Project MUSE., 2015)
Founded in 1927, Romania's Legion of the Archangel Michael was one of Europe's largest and longest-lived fascist social movements. This book approaches Romanian fascism by asking what membership in the Legion meant to young Romanian men and women. Viewing fascism from below, as a social category that had practical consequences for those who embraced it, the book shows how the personal significance of fascism emerged out of Legionaries' interactions with each other, the state, other political parties, families and friends, and fascist groups abroad.